Novel Intensive Care Unit (ICU) outreach service: Malaysian ICU nurses perspectives - Razak, Norasimah; Mohd Ali, Noor Azizah; Mohamed Ludin, Salizar (2013)
Background: The provision of ICU survivors that experience deterioration and ICU readmission has increased in recent years in Malaysia and various international studies has shown that ICU Outreach Services helps to improve patients’ condition, reduce length of hospital stay and reduction of mortality rate. Yet, little is known about the service and nurses perception towards ICU Outreach services.